DETERMINANT EFFICIENCY OF FINANCIAL INSTITUTIONS IN EMERGING MARKET - Suwinto Johan (Jurnal Manajemen dan Pemasaran Jasa, 2019)
The aim of this research is to analyze the determinants of non-bank financial institution efficiency. The non-bank financial industry is one of the main contributors to Indonesia economic growth during the last 15 years. The non-bank financial industry will the consumer finance company industry. The panel data used in this research is from 2001-2016.The non-bank financial industry is also measured as one the fastest raising industries in the last 16 years. Thesixmain financial ratios and related industry alliance impact the determinants of finance companies’ efficiency. The financial ratios are firm size, capital structure, equity, asset ratio, income to total assets and cost to total assets. The empirical results show that the determinants of non-bank financial institution are income to total assets and cost to total assets.